BUSINESS ENGLISH: VIEWING ITS BENEFITS IN THE PERSPECTIVES OF STUDENTS AND ALUMNI - Indrianti, Titien; Husniyah, Af’idatul (Jurnal Pendidikan Bahasa dan Sastra, 2020)
English has been a language for international business. Thus, English instruction should be directed to teaching communication skills necessary for business. As a vocational institution, State Polytechnic of Malang is supposed to view its English instruction from the perspectives of the students and alumni. Thus, the present study is intended to investigate the students’ and alumni’s perspectives on the benefits of Business English as well as their recommendation for the course. The respondents of this study are students and alumni of Business Administration Department, State Polytechnic of Malang. To tap the data, questionnaires are deployed. The data, then, are analyzed employing descriptive statistics to obtain the most and least typical responses. Findings indicate that both students and alumni take the benefit of the course. They view this subject is to prepare for their career development in the workplace. Besides, it is beneficial for their communication at the office, particularly in foreign companies. Alumni claim that their business English knowledge and skills during their college time are applicable in their workplace.  The respondents mostly demand more practices on business communication skills and vocabulary teaching included in Business English courses.